Curcumin to Promote the Synthesis of Silver NPs and their Self-Assembly with a Thermoresponsive Polymer in Core-Shell Nanohybrids - Soto-Quintero, Albanelly (Sci Rep, 2019)
This work presents a simple one-pot protocol to achieve core-doped shell nanohybrids comprising silver nanoparticles, curcumin and thermoresponsive polymeric shell taking advantage of the reducing properties of phenolic curcumin substance and its ability to decorate metallic surfaces. Silver nanoparticles were synthesized, via sodium citrate and silver nitrate addition into a boiling aqueous solution of curcumin, monomers and surfactant. Curcumin and sodium citrate promoted silver nucleation, acting as reducing and stabilizing agents. These curcumin-capped AgNPs enabled, after adding the radical polymerization initiator, the assembling of the growing polymer chains around the hydrophobic AgNP surface. The resultant core-doped shell nanohybrids exhibit plasmonic, luminescent and volume thermoresponsive properties, with improved possibilities to be used as successful therapeutic platforms. In fact, the possibility to nanoconfine the synergistic antioxidant, antiviral, antibacterial features of silver and curcumin in one bioavailable hybrid paves the way to promising applications in the biomedical field.